Karnataka Annual Plan 1980-81 Volume-II Statistical Statements - Government of Karnataka (Government of Karantaka, 1979)
The Karnataka Annual Plan 1980-81 (Volume II) presents a detailed statistical analysis and financial overview of the state’s development initiatives, highlighting sector-wise allocations, physical targets, and monitoring mechanisms. With a total state plan outlay of Rs. 27,121.72 lakhs, supplemented by pending approvals for irrigation projects, the plan prioritizes agriculture, water resources, transport, education, health, and social welfare. Key proposals include integrated rural development, employment generation programs, tribal sub-plans, and targeted investments in infrastructure such as roads, bridges, urban sanitation, and housing. The five-year plan framework (1978–1981) emphasizes inclusive growth, focusing on welfare programs for underprivileged groups, including scholarships, vocational training, healthcare improvements, and affordable housing for marginalized communities. Statistical statements (GN-1 to GN-6 and TSP-1) provide a basis for monitoring planned versus actual performance, ensuring accountability and effectiveness in public expenditure. Overall, the plan reflects Karnataka’s strategic approach to balanced socio-economic development, addressing both immediate and long-term objectives while fostering equitable growth and sustainable infrastructure development.
Government of Karnataka, Planning Department
Government of Karnataka, Planning Department
Keywords: Karnataka; State Plan; Agriculture; Irrigation; Health Services; Education; Housing; Urban Development; Tribal Welfare; Employment Generation; Infrastructure